JUECES DE PAZ EN EL CONOCIMIENTO DE INFRACCIONES RELATIVOS A LA VIOLENCIA FAMILIAR Y A LOS JUICIOS DE ALIMENTOS - Gordillo Noboa, Jaime Patricio (2016)
The thesis entitled "Justices knowledge of crimes relating to domestic violence and judgments of food," emerges as the result of the study of new legal concepts associated with new mechanisms for conflict resolution, such as justice of peace, although it is already running in other neighboring countries, this legal concept is relatively new in our country, which determines that there are still loopholes to be filled after the legal analysis. Thus, by analyzing the Organic Code of the Judiciary and the corresponding functions of Justices of the Peace and competition rules, in contrast to international law, it has been observed that, although our legislation does not provide the possibility that a magistrate knows offenses relating to family violence and food, if this is possible in other legislation, with certain restrictions so as not to get into contradictions of competent jurisdiction. This allowed doctrinaire obtain all information relevant to these themes and neighboring normativities in order to form a judgment and contrast it with the reality of our town, to thereby be able to obtain actual data regarding the views on this subject our society and to make it manifest in the conclusions and recommendations of this research work. Thus a systematic study of concepts, doctrine, national and international laws, surveys and interviews that reflect feelings of the people, and especially the possibility to give the legislature an alternative solution to the problem posed in this study is then developed as part my support for the advancement of standards in justice of the peace in our country.